2013
DOI: 10.1371/journal.pone.0080748
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thinning and Clinical Heterogeneity in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) has heterogeneous clinical features that could be translated into specific patterns of brain atrophy. In the current study we have evaluated the relationship between different clinical expressions of classical ALS and measurements of brain cortical thickness. Cortical thickness analysis was conducted from 3D-MRI using FreeSurfer software in 29 ALS patients and 20 healthy controls. We explored three clinical traits of the disease, subdividing the patients into two groups for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 37 publications
(48 reference statements)
14
56
0
Order By: Relevance
“…In the UMN and LMN ALS variants, we found significant correlations between disease duration, the absolute decrease in ALS-FRS-R, and progression with various brain regions. Some of these results have been reported in previous cross-sectional studies [13,16,19,35,36].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the UMN and LMN ALS variants, we found significant correlations between disease duration, the absolute decrease in ALS-FRS-R, and progression with various brain regions. Some of these results have been reported in previous cross-sectional studies [13,16,19,35,36].…”
Section: Discussionsupporting
confidence: 77%
“…All of these results have been well established in crosssectional studies [13][14][15][16][17][18][19]. Nevertheless, cortical thinning in ALS has rarely been demonstrated using a longitudinal approach.…”
Section: Introductionmentioning
confidence: 81%
“…Recently, Mezzapesa et al (2013) have confirmed the reduction in volume of the primary motor cortex in ALS patients compared with controls while Cosottini et al (2013) described the gray matter atrophy in motor and extra-motor areas of the cortex. Moreover, in ALS patients it has been found that the thinning of the primary motor cortex correlates with the progression of the disease (Lillo et al, 2012;Verstraete et al, 2010).…”
Section: Morphometric Changes In Mri Studymentioning
confidence: 88%
“…According to those data, the dominant hemisphere might be more impaired in structure and function when symptoms develop in patients with spinal onset ALS, and we speculate that perhaps for that reason, the degree of the non-dominant-side preservation represented by the NAA/Cr ratio is a better biomarker of vital prognosis. In fact, right frontal cortical thickness and disease severity might be related [35], and the right precentral gyrus cortex has been reported to be thinner in spinal-onset patients [36].We also found in our series that in treated patients, the baseline functional clinical parameters correlated bilaterally with the NAA/ Cr after 1 year of follow-up, but more strongly in the non-dominant motor gyrus, as if the initial functional state was also linked more with a metabolic improvement in the nondominant motor cortex after treatment.This raises some intriguing questions about why 1 year after treatment, the NAA/Cr ratio improved only on the dominant side and why correlations between the baseline NAA/Cr ratio on that side and clinical parameters 1 year later were stronger than on the non-dominant side. No definitive conclusion can be made, but following the same reasoning, we could speculate that the more impaired dominant side might also involve more room (or functionally silenced neurons) for functional improvement to reactivate these neurons, and, when less degenerated, the dominant motor gyri would be more primed for functional improvement.…”
Section: Discussionmentioning
confidence: 99%